Умови практичної стійкості дискретних систем і функції Ляпунова - Bashnyаkov, О. М.; Pichkur, V. V.; Khitko, I. V. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2012)
Building of optimal estimates of initial data sets and phase constraints for discrete systems with help of Lyapunov functions is considered. Optimal estimates of initial data sets in the form of a ball and ellipsoid classes are obtained for linear discrete systems with convex phase constraints.